PAI Learning Design Using the Addie Model in Welcome Material, O My Prophet, Beloved of Allah SWT at Wyata Dharma Middle School, Bandung - Mulyawan Safwandy Nugraha; Muhammad Kafnun Kafi; Ujang Dedih (al-Afkar, Journal For Islamic Studies, 2024)
This research is intended to describe the use of the ADDIE model in teaching Islamic Religious Education (PAI) with a focus on material regarding "Welcome to my Prophet, Beloved of Allah SWT." at Wyata Dharma Bandung Middle School. By applying a qualitative approach and analytical descriptive methods as the research foundation, main data was obtained through interviews, observation and documentation, while secondary data sources came from various relevant sources. The research results indicate that the application of the ADDIE model in PAI learning has proven to be very effective at Wyata Dharma Bandung Middle School. Through these ADDIE steps, students succeeded in understanding the material "Welcome to My Prophet, Beloved of Allah SWT." and apply it in everyday life, reflected in honest behavior, responsibility, fortitude, optimism and fair behavior.